THE CHICKLIT OR TEENLIT: A SYMBOL OF TEENAGERS MOVEMENT IN INDONESIAâS LITERATURE - Agustina, Hiqma Nur (Pusat Pengembangan Bahasa IAIN Tulungagung, 2017)
One of the genres of literature which becomes the trending topic in Indonesia is Chicklit or Teenlit. It reveals about young women and their life in many aspects. Mostly the arise of the new writers supported by the media, both electronic or printed, which become the tool to make them famous. Mediaâs power has taken a part to create their existence, mostly they are young generations in Indonesia; they also contribute the growth of the creative industry. They just became the new public figures like actress or actors who dominate the news in media. This paper is intended to analyze the signifcant role of media in creating the young new writers in Indonesia, especially one outstanding name, Debbie Widjaja. She has written four novels categorized as Teenlit. The qualitative method, the media, and societyâs theory will be used to analyze this research. The results of this study showed the mediaâs role give the important part in creating the new public fgures in Indonesia. The media has a strong power to embody someoneâs dream to be true in a good and potential way. Media construct peopleâs life from zero to be hero. By having this profession, as a young, fresh, and prospective writer, she has inspired many teenagers in Indonesia. Since there isnât any strict limitations or ideal criteria to produce Teenlit, everybody who fulflled the publisherâs criteria can publish their writings. This becomes the new movement for young generations in Indonesia to have a career in literature world.